Gårdsbaserade system för spannmålshantering i den framtida Lantmännenorganisationen - Wildt-Persson, Erik (2006)
The Swedish cooperative Lantmännen Ekonomiska Förening has initiated a project labelled "Operation Blåljus" that includes an extensive program for closing down elevators. The number of elevators will be reduced from 92 to approximately 15 after harvest of 2007. The objective of Blåljus is to increase the price of grain with 10 öre/kg. A project has been initiated at the Lantmännen Grain division where the purpose is to provide the farmers with support in their decisions and practical advice how they can load a 35 ton grain truck on 30 minutes. The result from the project will serve as a support system to the farmer in his ambition to achieve cost efficient systems to load a truck with grain on the farm. This master thesis is an economic evaluation of different systems for farm based grain handling.